Smart AD and DA Conversion - van Roermund, Arthur; Hegt, Hans.; Harpe, Pieter; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
While technology evolution is beneficial for digital circuits, it can cause performance limitations for analog circuits. To benefit from the technology evolution for analog circuits as well, the smart concept aims at improving the analog performance by using digital intelligence. In Smart AD and DA Conversion, the smart concept is applied to AD and DA converters by using on-chip intelligence to detect analog imperfections and to correct for them. First, general trends and challenges in data converter design are studied and a generalized view on smart conversion is introduced. Then, the smart concept is applied to solve specific imperfections in two design examples: a sub-binary variable-radix current-steering DA converter and a time-interleaved open-loop track&hold circuit. In both cases, the developed concepts are supported by theory and implemented test chips. The examples show that the smart concept can be successfully applied to improve the performance of AD and DA converters with respect to chip area, power consumption, static accuracy and/or dynamic accuracy.
AD and DA Conversion -- Smart Conversion -- Smart DA Conversion -- Design of a Sub-Binary Variable-Radix DAC -- Smart AD Conversion -- Design of an Open-Loop T&H Circuit -- T&H Calibration -- T&H Calibration for Time-Interleaved ADCs -- Conclusions.
Keywords: Engineering; Systems engineering; Engineering; Circuits and Systems; Solid State Physics